(untitled) (Research, Society and Development, 2022)
Historically, training in Dentistry has been predominantly technical, highly focused on the execution of clinical procedures, with professional guidance approaches reserved for specific moments of the courses. The objective of the present study was to evaluate the behavior of students in the final year of undergraduate and postgraduate students in Dentistry in the face of problem situations related to the ethical and legal exercise of the profession. A quantitative, observational, descriptive and analytical study was carried out, structured in a form containing ten problem situations that could occur in daily professional practice. The situations were about treatment abandonment, professional error, reversal of the burden of proof, term of dental contracts, request for withdrawal of documentation, ethical relationship, data for making a business card, general practitioner performing specialized procedure, professional secrecy and dental certificates. The sample consisted of 88 participants, being 61 academics and 27 professionals. The collection took place in two educational institutions, one public and one private. The data obtained were analyzed using the EPI INFO and Bio Estat 5.0 programs, considering a significance level of 5%. The results showed that of the 10 problem situations, the answer considered ideal prevailed in only 4 questions. In the association analysis, there was a better performance of women, linked to or graduated from a public institution and aged over 22 years. It is concluded that the conduct of the evaluated ones was varied in the face of problem situations, demonstrating that, in the sample considered, there was no formative standardization related to the ethical and legal practice of Dentistry.